The Effect of Tax Planning, Income Smoothing, And Capital Structure on Company Value with Good Corporate Governance as Moderating Variables (Empirical Study on Infrastructure, Utilities and Transportation Sector Companies Listed in IDX Period 2016 – 2019) - Leo Nardus Rowa Lewar; Agustin Fadjarenie (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study explains the effect tax planning, income smoothing, and capital structure on firm value with moderating variable good corporate governance. The research sample uses companies listed on the IDX for the years 2016–2019 period sector Infrastructure, Utilities and Transportation. An example of 39 companies was obtained using purposive sampling. The information used in the study looks at secondary information amassed through documentation techniques. In this research, the analysis method statistics used is the SPSS 24 application. The results of the hypothesis test illustrate that partially, tax planning does not affect firm value, income smoothing has no effect on firm value, capital structure affects firm value, and Good Corporate Governance cannot moderate the effect of planning profit and income smoothing on firm value, Good Corporate Governance can moderate the effect of capital structure on firm value.